Türkiye Wealth Fund - Muhammet Durdu (Invest Journal of Sharia & Economic Law, 2025)
Sovereign wealth funds (SWFs) are investment funds owned by states to implement various state objectives. SWFs date back to the 19th century, but their modern examples emerged in 1953 with the Kuwait Investment Authority. They have been extensively known in the financial world after the millennium but were not coined until 2005. They reached approximately 14 trillion USD, a paramount capacity for international financial markets. They originally stemmed from fossil fuel revenues with stabilization and saving aims. As states recognize them, their aims and resources have diversified. Currently, they appear to be a varied bulk of investment tools managed by sovereign states. Their sole collective feature is the state ownership. Although they could resemble each other to some degree in a specific group, they are not a homogeneous group of investors. The Türkiye Wealth Fund (TWF) is a distinctive SWFs. Türkiye has not had ample reserves to build an SWF, but it has used its enterprises and borrowing to build an SWFs. There is considerable controversy regarding TWF in Türkiye. In this article, I endeavored to present a general picture of TWF and the controversy surrounding it. Considering the best practices, I attempted to recommend some things to TWF to contribute to its improvement in the right way.